Checklist of Chinese Isotomidae (Collembola) and a description of a new Subisotoma - Gao, Yan; Xiong, Yan; Potapov, Mikhail (Zootaxa, 2009)
A review of the historical research of Chinese Isotomidae and a checklist of the 70 species of Isotomidae recorded so far from China are given. Subisotoma quadrisensillata sp. nov. from Hainan province (South China) and Dong Nai Province (Southern Vietnam) is described and illustrated. The species is characterized by a disproportional set of sensilla on Abd.I–IV which has never been observed in the family Isotomidae so far.